Fundamentals of Entrepreneurship ETR 300 Snap shot photography / Abdillah Abdul Kadir…[et.al] - Abdul Kadir, Abdillah; Peng Guan, Eveana Crystle; Tagaak, Helene; Raduan, Mohammad Fathullah; Jawawie, Nur Adila; Suhaili, Siti Selawati (2010)
Families need photographs to capture the special moments of their lives. Families of professionals are busy, and if too much time goes by between photos, these moments are lost forever. Babies, especially, grow fast and parents need photos of them several times a’ year. While nearly everyone has a camera for snapshots, people need professional quality photos when they will be shown to an important audience, and when people want to be seen in the best light. The Internet has expanded the use of photos, making it possible for anyone to send them or to publish them for wide viewing. Professionals often have business needs for high-quality photos, and through this familiarity, they acquire a taste for them. When these professionals need photos to preserve memories, or to display family photos when they entertain at home, they have the budget and the desire for similarly high-quality photos. Just as they appoint their homes with fine furniture and decorations, the photos on their walls need to exhibit their standards of quality. Most people use professional photo studios only on rare occasions, such as weddings, yearbook pictures, or baby portraits. Because the client has to initiate the call, many special moments are lost and the studio loses potential business. Photo studios generally charge a large fee for CDs of their clients' digital images. For these reasons, most photo studios are rarely used by families as a whole.